The role of TP53 in miRNA loading onto AGO2 and in remodelling the miRNA–mRNA interaction network. (26th February 2015) - Krell, Jonathan; Stebbing, Justin; Frampton, Adam Enver; Carissimi, Claudia; Harding, Victoria; De Giorgio, Alexander; Fulci, Valerio; Macino, Giuseppe; Colombo, Teresa; Castellano, Leandro
Abstract: Background: DNA damage transactivates tumour protein p53 (TP53) -regulated surveillance, crucial in suppressing tumorigenesis. TP53 mediates this process directly by transcriptionally modulating gene and microRNA (miRNA) expression and indirectly by regulating miRNA biogenesis. However, the role of TP53 in regulating miRNA-AGO2 loading and global changes in AGO2 binding to its gene targets in response to DNA damage are unknown. These processes might be novel mechanisms by which TP53 regulates miRNAs in response to DNA damage. Methods: To show the network of miRNA–mRNA interactions that occur in response to DNA damage, we stimulated TP53 wild-type and null cell-lines with doxorubicin and performed RNA sequencing from total RNA (RNA-Seq) and AGO2-immunoprecipitated RNA (AGO2-RIP-Seq). We used a combined AGO2 RIP-seq and AGO2 PAR-CLIP-seq (photoactivatable-ribonucleoside-enhanced cross-linking and immunoprecipitation) approach to determine the exact sites of interaction between the AGO2-bound miRNAs and their mRNA targets. Findings: TP53 directly associated with AGO2, and induced and reduced loading of a subset of miRNAs, including the lethal 7 (let-7) miRNA family members, onto AGO2 in response to DNA damage. Although mutated TP53 maintained its capacity to interact with AGO2, it mediated unloading instead of loading of let-7 family miRNAs, thereby reducing their activity. We determined the miRNA–mRNA interaction networks involved in the response to DNA damage both in the presence and absence of TP53 . Furthermore, we showed that miRNAs whose cellular abundance or differential loading onto AGO2 was regulated by TP53 were involved in an intricate network of regulatory feedback and feedforward circuits that fine-tuned gene expression levels in response to DNA damage to permit the repair of DNA damage or initiation of programmed cell death. Interpretation: Control of AGO2 loading by TP53 is a new mechanism of miRNA regulation in carcinogenesis. Funding: UK Medical Research Council, Action Against Cancer.